Towards Financial Semiology. (July 2019) - Hayoun, Shaul
Abstract: This paper offers a new avenue in contemplating semiology beyond linguistics: it introduces accounting as ' Financial Semiology '. The paper discusses the implications of a semiological theorisation of accounting, particularly in problematising the conventional assumptions underlying two important accounting issues: recognition and measurement of the firm's assets, specifically with respect to the notion of alleged 'representation' of assets and their seemingly 'intrinsic value'. Through two core pillars in Saussure's semiology, re-titled here as 'reciprocal articulation' and 'value constellation', the paper offers an alternative theorisation of such accounting procedures. The paper also shows the implications of such Financial Semiology for the general theory of semiology, and distils its core characteristics as a framework for explicating the non-substantive operation of social sign systems. Highlights: Accounting is the one truly extra-linguistic semiology: a Financial Semiology . Instead of 'representation', accounting manifests semiology's 'articulation'. Instead of intrinsic value, accounting manifests semiology's 'value constellation'. Accounting explicates the non-substantive operation of semiological systems.